2011
DOI: 10.3844/ajabssp.2011.162.171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Edible Coatings, Storage Time and Maturity Stage on Overall Quality of Tomato Fruits

Abstract: Problem statement: Tomato (Lycopersicon esculentum Mill.) is one of the most widely consumed fresh vegetables in the world; however, its highly perishable nature limits its postharvest life. Major losses in tomato quality and quantity occur between harvest and consumption. Therefore, the application of new technologies to extend the postharvest life of this commodity is needed. The use of edible coatings appears to be a good alternative. Approach: We evaluated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 33 publications
6
22
0
1
Order By: Relevance
“…Phenolic and flavonoid compounds are secondary metabolites in plants with the ability to protect human body tissue against oxidative attacks (Romanazzi et al 2002). However, even when the use of mineral oil and carnauba edible coatings modifies the metabolism of tomato with positive effects on the organoleptic quality of the fruit (Dávila-Aviña et al 2011), there is a stress that alters the production of secondary metabolites, as found in this study.…”
Section: Total Phenols and Flavonoidssupporting
confidence: 52%
See 2 more Smart Citations
“…Phenolic and flavonoid compounds are secondary metabolites in plants with the ability to protect human body tissue against oxidative attacks (Romanazzi et al 2002). However, even when the use of mineral oil and carnauba edible coatings modifies the metabolism of tomato with positive effects on the organoleptic quality of the fruit (Dávila-Aviña et al 2011), there is a stress that alters the production of secondary metabolites, as found in this study.…”
Section: Total Phenols and Flavonoidssupporting
confidence: 52%
“…Samples were washed using chlorinated water (200 ppm) for 2 min and then left to dry at room temperature for 1 h. Fruit samples were classified according to their size, uniformity and maturity stage (2 and 4). At stage 2 (i.e., "breaker"), fruits showed less than 10 % green color, while at stage 4 (i.e., "pink"), fruits showed a color other than green on less than 30-60 % of the surface of the whole fruit (Dávila-Aviña et al 2011). …”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between enzymatic activity and firmness loss has been evaluated by Dávila‐Aviña et al (), on tomatoes coated with carnauba wax and mineral oil, they reported a reduction in pectin‐methylesterase activity with simultaneous lowering on the firmness decay in coated samples when compared to uncoated ones.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of weight loss in strawberry fruit with 2% chitosan coating caused by the loss of water in strawberries. Meanwhile, in strawberries with 3% coat kitoasan there is a thicker layer of barrier that protects the fruit so it can suppress the evaporation of water content in strawberries [8]. This can be compared also with strawberry control (without coating) which experienced the greatest weight loss rate.…”
Section: Weight Lossmentioning
confidence: 99%